2013
DOI: 10.1186/2046-2395-2-14
|View full text |Cite
|
Sign up to set email alerts
|

Life-long spontaneous exercise does not prolong lifespan but improves health span in mice

Abstract: BackgroundLife expectancy at birth in the first world has increased from 35 years at the beginning of the 20th century to more than 80 years now. The increase in life expectancy has resulted in an increase in age-related diseases and larger numbers of frail and dependent people. The aim of our study was to determine whether life-long spontaneous aerobic exercise affects lifespan and healthspan in mice.ResultsMale C57Bl/6J mice, individually caged, were randomly assigned to one of two groups: sedentary (n = 72)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 59 publications
5
64
0
Order By: Relevance
“…However, the antioxidant diet had no effect on longevity of the runners, stating that the caloric deficit induced by exercise in male rats does not have a life-extending effect that is countered by oxidative tissue damage (Holloszy 1998). In mice, life-long spontaneous exercise was found not to prolong lifespan but to improve health span (Garcia-Valles et al 2013). In this study voluntary running did prevented several aging-related signs of frailty (such as decreases in strength, endurance and motor coordination), which was accompanied by a significant increase in mitochondrial biogenesis in skeletal muscle.…”
Section: Physical Activitymentioning
confidence: 99%
“…However, the antioxidant diet had no effect on longevity of the runners, stating that the caloric deficit induced by exercise in male rats does not have a life-extending effect that is countered by oxidative tissue damage (Holloszy 1998). In mice, life-long spontaneous exercise was found not to prolong lifespan but to improve health span (Garcia-Valles et al 2013). In this study voluntary running did prevented several aging-related signs of frailty (such as decreases in strength, endurance and motor coordination), which was accompanied by a significant increase in mitochondrial biogenesis in skeletal muscle.…”
Section: Physical Activitymentioning
confidence: 99%
“…Interestingly, the decline in muscle PGC-1α levels with aging is attenuated by caloric restriction (CR) and exercise (Derbre et al, 2012; Garcia-Valles et al, 2013). …”
Section: Biomarkers Of Nmj In Aging and Signaling Pathwaysmentioning
confidence: 99%
“…It should be noted that although most studies indicate that antioxidants protect against oxidative stress and thus extend lifespan (Anisimov et al ., 2011; Niu et al ., 2013) and lead to enhanced exercise capacity (Ji et al ., 1998), recently some reports indicated that antioxidants have no beneficial effects on exercise or are even harmful in high concentrations (Selman et al ., 2013). In addition, although a number of studies have reported that exercise leads to increased longevity (Holloszy, 1998; Navarro et al ., 2004; Barnes, 2015), one study in mice is not in agreement (Garcia‐Valles et al ., 2013). However, the overwhelming preponderance of data in patients support the concept that exercise improves not only healthy lifespan, but also longevity, as it clearly is protective against cardiovascular disease, diabetes, and obesity, all of which are known to reduce lifespan.…”
Section: Discussionmentioning
confidence: 99%